Simulasi Persamaan Difraksi Fraunhofer pada Celah Lingkaran dengan Menggunakan Visual Basic for Application (VBA) Spreadsheets Excel - Nurdianto, Nurdianto; Safiuddin, La Ode; Eso, Rosliana (Jurusan Pendidikan Fisika, 2020)
The research aims to visualize the Fraunhofer Diffraction Equation in the Circle Slit using Excel Spreadsheets and Macro Visual Basic for Application (VBA). The results of this study indicate that Microsoft Excel is able to display a visualization of fraunhofer diffraction shapes on the circle slit. The results of this study can also show a simulation of the formation of fraunhofer diffraction in a slit circle with a gap width (a) and a different wavelength (Î»).